2006
DOI: 10.1186/1471-2091-7-7
|View full text |Cite
|
Sign up to set email alerts
|

The protein kinase DYRK1A phosphorylates the splicing factor SF3b1/SAP155 at Thr434, a novel in vivo phosphorylation site

Abstract: BackgroundThe U2 small nuclear ribonucleoprotein particle (snRNP) component SF3b1/SAP155 is the only spliceosomal protein known to be phosphorylated concomitant with splicing catalysis. DYRK1A is a nuclear protein kinase that has been localized to the splicing factor compartment. Here we describe the identification of DYRK1A as a protein kinase that phosphorylates SF3b1 in vitro and in cultivated cells.ResultsOverexpression of DYRK1A caused a markedly increased phosphorylation of SF3b1 in COS-7 cells as assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 33 publications
(63 reference statements)
1
47
0
3
Order By: Relevance
“…The substrate specificities identified from HeLa cell extracts correlate well with previous studies that have identified DYRK1A substrates such as Tau (Ryoo et al., 2007; Liu et al., 2008), amphiphysin (Murakami et al., 2006), and caspase 9 (Seifert et al., 2008) that conform to the above definition (proline at P+1 position and arginine at P− positions), whereas other studies report substrates such as spliceosomal protein SF3b1 (de Graaf et al., 2006) that contain proline in the P+1 position but not basophilic residues at P− positions. Furthermore, DYRK1A substrates α-synuclein (Kim et al., 2006) and p53 (Park et al., 2010) do not contain either of these substrate specificity determinants, indicating the flexibility of DYRK1A in substrate recognition.…”
Section: Resultsmentioning
confidence: 91%
“…The substrate specificities identified from HeLa cell extracts correlate well with previous studies that have identified DYRK1A substrates such as Tau (Ryoo et al., 2007; Liu et al., 2008), amphiphysin (Murakami et al., 2006), and caspase 9 (Seifert et al., 2008) that conform to the above definition (proline at P+1 position and arginine at P− positions), whereas other studies report substrates such as spliceosomal protein SF3b1 (de Graaf et al., 2006) that contain proline in the P+1 position but not basophilic residues at P− positions. Furthermore, DYRK1A substrates α-synuclein (Kim et al., 2006) and p53 (Park et al., 2010) do not contain either of these substrate specificity determinants, indicating the flexibility of DYRK1A in substrate recognition.…”
Section: Resultsmentioning
confidence: 91%
“…We have found that Dyrk1A phosphorylates ASF mainly at three sites (Ser-227, Ser-234, and Ser-238) within the consensus motif (RX(X)(T/S)P) of Dyrk1A, none of which are known to be phosphorylated by the other four ASF kinases. In addition to ASF, Dyrk1A also phosphorylates other splicing factors and regulates their activity (20,21). However, whether phosphorylation of these factors plays any role in the alternative splicing of tau is not known yet.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple biological functions of Dyrk1A are suggested by its interaction with a myriad of cellular proteins including transcription and splicing factors (19). It is distributed throughout the nucleoplasm with a predominant accumulation in nuclear speckles (20,21), the storage site of inactivated SR proteins, including ASF. Because of its overexpression in DS brain and its predominant localization in nuclear speckles, we hypothesized that Dyrk1A could affect phosphorylation of ASF, and in doing so, disturb ASF-regulated alternative splicing of tau E10, leading to the apparent dysregulation of the balance of 3R-tau and 4R-tau.…”
mentioning
confidence: 99%
“…Our results provide additional evidence suggesting an essential role of Sap155 phosphorylation, namely NIPP1-⌬C constituted a hyper-active PP1 holoenzyme, decreasing hyperphosphorylated Sap155 and thereby inhibiting splicing. Sap155 has many potential phosphorylation sites, and several are phosphorylated in in vitro splicing reactions and also in vivo (36,37). Identification of Sap155 phosphorylation sites and their functions during splicing is critically important for understanding how Sap155 is regulated byphosphorylation/dephosphorylation.…”
Section: Discussionmentioning
confidence: 99%